Revitalization using university community partnerships: a case study of Fort Valley, Georgia - Jackson, Jael Patrice (Kansas State University, 2008)
This paper suggest that a force, when encompassed in a tripod body, the host town, the area community, and the University, can succeed in making necessary improvements to a struggling community, provided this effort is embedded in a shared conceptualization of revitalization planning that will enliven, regenerate, and produce. The result of this effort depends on the balanced exchange between the various stakeholders of higher education within the host communities, and local governments who can all share mutual responsibilities as planners while applying the concept of university community partnership to the City of Fort Valley, a target area and Fort Valley State University. The exchange between stakeholders is used to establish why they, as an inclusive community, should apply this model to distinguish each party's roles then determine the concepts and recommendations that could be utilized to accomplish the ultimate goal of revitalization.
Keywords: university community partnerships; Urban and Regional Planning (0999)